Identifikasi dan Potensi Perbanyakan Jamur Mikoriza Arbuskula dari Tanah Salin untuk Budidaya Sorgum (Sorghum bicolor L.) di Kabupaten Kupang - Marlin Marhaeni (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
The expansion of national food production is constrained by the predominance of marginal lands, particularly saline soils with low fertility and disrupted microbial activity. This study aimed to characterize the diversity of indigenous arbuscular mycorrhizal fungi (AMF) from saline soils in Kupang, East Nusa Tenggara, and to evaluate their potential as bioinoculants for sorghum (Sorghum bicolor L.). Saline soils with electrical conductivity (EC) ranging from 4.18 to 11.48 mmhos/cm were collected from six sites, each comprising five subsamples (totaling 30 samples). AMF spores were isolated through a combination of wet sieving (400–45 µm) and 60% sucrose centrifugation, followed by morphological identification under a compound microscope. A pot experiment was arranged in a Completely Randomized Design (CRD) with six treatments (five AMF spore types and a non-inoculated control) and six replications (n = 36). Five dominant spore types were identified based on color: yellow, orange, white, black, and reddish-brown. Orange and yellow spores were the most abundant (39–56% and 11–33% of total spores, respectively) and exhibited the highest sporulation rates, averaging 64.25 and 50.5 spores per 100 g of soil. Inoculation enhanced root colonization of sorghum, reaching 61% with orange spores and 58% with yellow spores, compared with 24% in the control. Plant growth was also significantly improved: orange spores produced the tallest plants (79 ± 3.1 cm), while yellow spores yielded the highest leaf number (6.0 ± 0.5 leaves/plant), compared with the control (58 ± 2.7 cm and 5.0 ± 0.4 leaves/plant, respectively). These findings demonstrate that indigenous AMF spores, particularly the yellow and orange types, which are presumably in the genus Glomus, are highly adaptive to saline conditions and significantly enhance sorghum growth. This highlights their potential as locally sourced biofertilizers to improve crop productivity on saline marginal lands. Further molecular identification and multi-season field trials are recommended to validate their efficacy and broaden their application to other salt-tolerant crops.